Linking instruments in development and foreign policy: Comprehensive approaches in the EU - Christel Vincentz Rasmussen (Danish Institute for International Studies (DIIS), 2013)
The EU is currently working at defining a comprehensive approach linking development and other instruments in external action. The Lisbon Treaty has contributed to a reorganisation of the institutions in Brussels, affecting crisis management structures and the organisation of external relations. Comprehensive approaches are not new in the EU system, in particular an integrated approach for conflict prevention and a concept for civil-military coordination were developed in the 2000s. However, a forthcoming communication on a comprehensive approach in external action constitutes an occasion to clarify and operationalise the approach in a new, post-Lisbon, institutional setting as well as consolidating the formal EU commitment to working comprehensively. The study argues that building a comprehensive approach is a long-term process with changing objectives and focus over time in response to an evolving context. An essential building block of a comprehensive approach is cross-sector collaboration involving different units and agencies of the EU at headquarters and field level. ...
Keywords: 300